Detection and isolation of digital dermatitis treponemes from skin and tail lesions in pigs. (February 2016) - Clegg, Simon R.; Sullivan, Leigh E.; Bell, Jennifer; Blowey, Roger W.; Carter, Stuart D.; Evans, Nicholas J.
Abstract: Pig skin lesions are common significant welfare issues, and can cause large economic losses, due to culling of severely affected animals or carcass condemnation at slaughter. It was considered that the treponemal bacteria associated with digital dermatitis (DD) lesions in cattle, sheep and goats may have a role in these pig lesions. Specific diagnostic PCR assays for three cultivable DD Treponema phylogroups were used to survey relevant porcine lesion samples. Using these assays, DD treponemes were detected in 88% (22/25), 72% (8/11) and 82% (14/17) of tail, ear and flank lesions, respectively. Mouth swabs from animals kept in enclosures with high prevalence of skin lesions were positive for the DD treponemes, but not in enclosures with low lesion prevalence. Culture of treponemes from skin lesions resulted in pure isolates of all three DD-associated phylogroups. This study shows a strong association of DD treponemes with a range of pig skin lesions. Highlights: Pig skin lesions from the tail, flank and ear were sampled. All lesions were tested for the presence of digital dermatitis treponemes. DD treponemes were detected in over 70% of each lesion. The presence of treponemes in the mouth offers a potential transmission route. Same bacteria found in animals with multiple lesions suggest movement of bacteria.